The Mass of a Wrecked Ship is Bones and Water: Thoughts on Dominique White’s "Deadweight" - Marta Espiridião (Journal of Science and Technology of the Arts, 2024)
This essay examines Dominique White's recent solo exhibition at Whitechapel Gallery, exploring how her sculptures evoke histories of transatlantic slavery and colonial systems, and the enduring impacts of displacement. Drawing from afrofuturism and hydrarchy, White's works transform iron, ropes, and driftwood into haunting forms that resemble the wreckage of ships and the skeletal remnants of maritime violence. Central to the exhibition Deadweight is the interplay between materiality and memory, effectuated in the act of immersing her sculptures in the Mediterranean Sea, allowing salted water to erode and "cleanse" their surfaces, fleshing out layers of history, trauma, and renewal. The works presented confronted viewers with their imposing presence, balancing destruction and transformation, all while configuring a poetic reimagining of the historical entanglements between the century-old European capitalist project and its lasting repercussions on peoples from the African continent envisioning an "alternative future" forged from the remnants of the devastation of our colonial past.